2020
DOI: 10.4218/etrij.2020-0210
|View full text |Cite
|
Sign up to set email alerts
|

Combined time bound optimization of control, communication, and data processing for FSO‐based 6G UAV aerial networks

Abstract: Because of the rapid increase of mobile traffic, flexible broadband supportive unmanned aerial vehicle (UAV)‐based 6G mobile networks using free space optical (FSO) links have been recently proposed. Considering the advancements made in UAVs, big data processing, and artificial intelligence precision control technologies, the formation of an additional wireless network based on UAV aerial platforms to assist the existing fixed base stations of the mobile radio access network is considered a highly viable optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…It can be seen from Figure 13 that as the electronic countermeasure event intelligence data increases, the signalto-noise ratio of the electronic countermeasure event intelligence processing results of different methods decreases. When the electronic countermeasure event intelligence data is 5000 MB, the signal-to-noise ratio of the electronic countermeasure event intelligence processing result of reference [4] method is 24.8 dB, and the signal-to-noise ratio of the electronic countermeasure event intelligence processing result of reference [5] method is 23.4 dB. e signal-to-noise ratio of the electronic countermeasure event intelligence processing result of the proposed method is 30 dB.…”
Section: Stability Comparison Of Information Processing Results Ofmentioning
confidence: 98%
See 2 more Smart Citations
“…It can be seen from Figure 13 that as the electronic countermeasure event intelligence data increases, the signalto-noise ratio of the electronic countermeasure event intelligence processing results of different methods decreases. When the electronic countermeasure event intelligence data is 5000 MB, the signal-to-noise ratio of the electronic countermeasure event intelligence processing result of reference [4] method is 24.8 dB, and the signal-to-noise ratio of the electronic countermeasure event intelligence processing result of reference [5] method is 23.4 dB. e signal-to-noise ratio of the electronic countermeasure event intelligence processing result of the proposed method is 30 dB.…”
Section: Stability Comparison Of Information Processing Results Ofmentioning
confidence: 98%
“…Electronic Countermeasure Incidents. Based on the electronic countermeasure event intelligence data, the proposed method, reference [4] method, and reference [5] method are used to process the electronic countermeasure event intelligence, and the comparison results of the stability of the electronic countermeasure event intelligence processing results of different methods are obtained as shown in Figure 13.…”
Section: Stability Comparison Of Information Processing Results Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, real-time big data processing technologies OptEx [13], SAF [14], SRSAF [15], and TSAF are compared using MATLAB 2020a based simulation. Most of the simulation parameters were performed according to the basic environment of Apache Spark Streaming.…”
Section: Simulation and Discussionmentioning
confidence: 99%
“…The development trend of artificial intelligence and wireless network communication is unstoppable. We have found that the application of artificial intelligence and wireless network communication in interactive installation art can make us interact better and truly understand the emotions and art expressed by the installation [15]. The following is the connection between artificial intelligence and wireless network as shown in Figure 3.…”
Section: Methods and Related Conceptsmentioning
confidence: 98%